Finnish Variant of Late Infantile Ceroid Neuronal Lipofuscinosis (fvLINCL); Atypical Finding on Magnetic Resonance Imaging - Antonio Gomes Lima Júnior (Shahid Beheshti University of Medical Sciences, 2021)
Ceroid neuronal lipofuscinosis (CLN) is a rare group of autosomal recessive neurodegenerative diseases that cause developmental delay and seizures. Herein, we present a case of a 7-year-old girl who referred for magnetic resonance imaging (MRI) following cognitive impairment and seizures. MRI was performed demonstrating some usual findings, and, surprisingly, a normal-sized cerebellum. This case draws attention to not hold to just the classical imaging presentation in order to suspect some leukodystrophy.